Mitigating Increased Cardiovascular Risk in Patients with Obstructive Sleep Apnea Using GLP-1 Receptor Agonists and SGLT2 Inhibitors: Hype or Hope? - Paschalis Karakasis; Marios Sagris; Dimitrios Patoulias; Theocharis Koufakis; Panagiotis Theofilis; Aleksandra Klisic; Nikolaos Fragakis; Mohamed El Tanani; Manfredi Rizzo (Biomedicines)
Obstructive sleep apnea (OSA) is a prevalent condition associated with increased cardiovascular risk, particularly in individuals with comorbid obesity and type 2 diabetes (T2D). Despite the widespread use of continuous positive airway pressure (CPAP) for OSA management, adherence remains suboptimal, and CPAP has not consistently demonstrated reductions in surrogate cardiovascular events. Recently, attention has focused on glucagon-like peptide-1 receptor agonists (GLP-1RAs) and sodium-glucose cotransporter-2 (SGLT2) inhibitors as potential therapeutic agents for mitigating cardiovascular risk in OSA patients. These agents, originally developed for T2D management, have demonstrated pleiotropic effects, including significant weight loss, blood pressure reduction, and amelioration of endothelial dysfunction and arterial stiffness, along with anti-inflammatory benefits, which may be particularly beneficial in OSA. Emerging clinical evidence suggests that GLP-1RAs and SGLT2 inhibitors can reduce OSA severity and improve daytime sleepiness, potentially reversing the adverse cardiovascular effects observed in OSA. This review explores the pathophysiological mechanisms linking OSA with cardiovascular disease and evaluates the potential therapeutic roles of GLP-1RAs and SGLT2 inhibitors in addressing cardiovascular risk in OSA patients. Further research, including long-term clinical trials, is necessary to establish the effectiveness of these therapies in reducing cardiovascular events and improving patients’ reported outcomes in this population.